Foot contact timings and step length for sprint training - Evans, M.; Colyer, S. L.; Cosker, D.; Salo, A. (IEEE Workshop on Applications of Computer Vision, 2018)
The frequency and length of a runner's steps are fundamental aspects of their performance. Accurate measurement of these parameters can provide valuable feedback to coaching staff, particularly if regular measurement can be made and monitored over the course of a season. This paper presents a computer vision based approach using high framerate cameras to measure the location and timing of foot contacts from which step length and frequency can be determined. The approach is evaluated against force-plates and optical motion capture for a mix of 18 trained and recreational runners. Force-plates and optical motion capture are considered to be the current "gold-standard'' in biomechanics, and this is the first vision based paper to evaluate against these standards. Landing and take-off times were shown to be measurable to within 1.5 frames (at 180fps) and step length to within 1 cm.